2000
DOI: 10.1021/ol005777b
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Functionalized Oxazolines and Oxazoles with DAST and Deoxo-Fluor

Abstract: [formula: see text] A mild and highly efficient cyclization of beta-hydroxy amides to oxazolines is described using DAST and Deoxo-Fluor reagents. A one-pot protocol for the synthesis of oxazoles from beta-hydroxy amides is also presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
234
0
5

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 445 publications
(241 citation statements)
references
References 26 publications
2
234
0
5
Order By: Relevance
“…2 The second building block, corresponds to an oxazole or thiazole ring, and was synthesized from serine dipeptides. 3 Using this aproach, we proposed 4 zones which can be appropiate for modifications. This way, we synthesized 16 new compounds, and they were assayed in vitro to determine their antiproliferative activity against five human solid tumor cell lines.…”
Section: Resultsmentioning
confidence: 99%
“…2 The second building block, corresponds to an oxazole or thiazole ring, and was synthesized from serine dipeptides. 3 Using this aproach, we proposed 4 zones which can be appropiate for modifications. This way, we synthesized 16 new compounds, and they were assayed in vitro to determine their antiproliferative activity against five human solid tumor cell lines.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the considerable instability of the 2-vinyloxazole moieties under basic and dehydration conditions, we planned to introduce the vinyl group to the oxazole ring after construction of the tris-oxazole structure. Dehydrating cyclization of 4 by diethylaminosulfur trifluoride (DAST) 17 gave an oxazoline intermediate (85%), which was oxidized with a combination of bromotrichloromethane and 1,8-diazabicycloundec-7-ene (DBU) 18 at room temperature to give tris-oxazole 5 (98% based on recovered starting material). 19 We found that acetonitrile is a better solvent than the conventional CH 2 Cl 2 in this reaction.…”
Section: Pergamon Tetrahedron Lettersmentioning
confidence: 99%
“…[15][16][17] We, however, have found that our fluorinated derivatives (7)(8)(9)(10)(11)(12) were readily hydrolyzed and solvolyzed at room temperature confirming the enhanced eletrophilicity of C 2 and thereby allowing an easy opening of the heterocyclic ring. Difluoroacids (13)(14)(15)(16) were produced in water, difluoroesters (17)(18)(19)(20), in alcohols and difluoroamides (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) in amines. Esterified aminoacids (41) and thiosemicarbazides derivatives (42-46) were obtained on reaction with thiosemicarbazides.…”
Section: Reactions Of 7-12 With Nucleophilesmentioning
confidence: 99%
“…IR (KBr) max /cm -1 : 3321 (NH), 1673 (COMe), 1079 (CF 2 ). m/z (%): 298 (17), 256 (7), 238 (12), 198 (8), 183 (26), 164 (3), 156 (100), 137 (19), 109 (7), 74 (14). 1 9.62 (bs, NH).…”
Section: -(2-acetamido-5-methylphenyl)-n-butyl-22-difluoroacetamideunclassified